The Impact of Total Employee Involvement and Management Leadership on the Healthcare Effectiveness inYemen - et.al, M Abobakr S. S. Ahmed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was developed for the purpose of finding out the impact of total employee involvement and management leadership on organizational effectiveness in the health sector in Yemen. The main problem of this research was found based on the research of Dureab et al. (2020) who indicated that the healthcare services in Yemen lack effectiveness, specifically over the COVID-19 crisis. The healthcare sector suffered from the high demand for its services, which almost become out of control. For this research, it was decided to use the quantitative approach. Because the quantitative approach was used, the data source will be primary data for this research. This research will use the questionnaire instrument to be the tool to collect the data. This research will be located at Sana’a city (the capital city in Yemen); because most of the healthcare institutions are located there. These questionnaires were distributed to the research samples, who were having the size of 379 employees in the healthcare institutions in Yemen. Regression test has been used to conduct statistical analysis from the primary data. Several tests have been conducted for the collected data. The main results found that there is a positive and significant relationship between total employee involvement and organizational effectiveness in Yemen. Also, there is a positive and significant relationship between management leadership and organizational effectiveness in Yemen. It has been observed that healthcare professionals in this group perceive the quality of health services they produce in their institutions as low. In order to eliminate this perception, it should be evaluated according to the leadership qualities of the managers selected under the responsibility of the top managers of the health institutions, and the workload should be reduced with the transfer of authority